Baicalin inhibits Salmonella typhimurium‐induced inflammation and mediates autophagy through TLR4/MAPK/NF‐κB signalling pathway. Issue 2 (4th October 2020) - Zhang, Ling; Sun, Yuan; Xu, Wei; Geng, Yu; Su, Yuhong; Wang, Qiuning; Wang, Jinli
Abstract: Baicalin has been reported to protect mice against Salmonella typhimurium ( S. typhimurium ) infection, while its molecular mechanisms are unclear. In this study, multiplicity of infection (MOI) and observation time were measured. Cell viability and LDH levels were examined in RAW264.7 cells and H9 cells. RAW264.7 cells were stimulated with S typhimurium in the presence or absence of Baicalin, and the levels of pro‐inflammatory cytokines were detected by enzyme‐linked immunosorbent assay (ELISA). The changes in reactive oxygen species (ROS) production were determined by fluorescence microscopy and ELISA. The autophagy and TLR4/MAPK/NF‐κB signalling pathway were examined by immunofluorescence microscopy, quantitative reverse transcription‐polymerase chain reaction and Western blotting. The results indicated that MOI of 30 and duration of autophagy evident at 5 h were applicable to this study. Baicalin prevented death of macrophages, promoted bactericidal activity, decreased the levels of pro‐inflammatory cytokines and ROS and reduced the changes of key biomarkers in autophagy and TLR4/MAPK/NF‐κB signalling pathway infected by S typhimurium . TLR4‐overexpressed cells, autophagy and TLR4/MAPK/NF‐κB signalling pathway were activated by S typhimurium, which was suppressed by Baicalin. Our findings indicated that Baicalin exerts anti‐inflammatory and cell‐protective effects, and it mediates autophagy by down‐regulating the activity of TLR4 infected by S typhimurium .